SNR Improvement Employing Dynamics Beamforming Based on Angle of Arrival for Mobile WiMax IEEE 802.16e - T. Yuwono (IAES Indonesia Section, 2014)
The development of telecommunicationtechnology and services is very rapid. One oftelecommunication technology that is beingdeveloped is WiMax (Worldwide Interoperabilityfor Microwave Access). The advantages of WiMaxis it possess much range and can operate in non -LOS conditions. So it fits implemented inIndonesia to accelerate the internet penetration.Some features of WiMax technology is higherbandwidth and further range/area. SNRImprovement is The effort to increase the rangeand improve the BER (Bit Error Rate). In thispaper, we propose the dynamics beamformingalgorithm to improve SNR in mobile WiMax.The algorithm will desire the best beamwidth andnumber of beam based on Angle of Arrival (AoA)of MS in the cell. In this paper, we also evaluatethe algorithm with compared to switched beamantenna. The simulation result shows thatdynamics beamforming have SNR performancebetter than switched beam antenna about 7dB.